A review on effects of using electrochemical extraction technique in corrosion treatment of reinforced concrete - Ismail, Mohammad; Yahaya, Nordin (Faculty of Civil Engineering, 2001)

(untitled)
Traditional patch repair of concrete suffers from corrosion of the reinforcements due to the presence of chloride which as penetrated beyond the reinforcement. Methods based on electrochemical technique either in the form of cathodic protection or electrochemical chloride extraction have been used to alleviate this problem. Since electrochemical chloride extraction is a new technique that adopts higher current density with short duration of treatment, this paper reviews the possible side effects that might be caused in using this technique. The review covers possible physical and chemical effects such as steel/concrete bond strength and alkali-aggregate reaction